Pengembangan media komik materi penjumlahan bilangan cacah kelas II SDN Randusari Yogyakarta - Egi Alridhayansah; Trisniawati Trisniawati; Mahmudah Titi Muanifah; Nelly Rhosyida; Dewi Anggreini (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to (1) develop a feasible learning comic media named KOJUMCAH (Whole Number Addition Comic) for second-grade students at SDN Randusari, (2) describe the feasibility of KOJUMCAH learning media (Whole Number Addition Comic) in the second grade of SDN Randusari, and (3) describe student responses to the use of educational comic media in learning whole number addition in the second grade of SDN Randusari. This research is a Research and Development (R&D) study. The development steps used are based on Borg and Gall's development procedure theory, limited to 7 steps: potential and problems, data collection, initial product development, expert validation, design revision, limited product trial, and revision of limited product trial results. This research was conducted at SDN Randusari with a subject of 8 second-grade students (limited product trial). Data collection techniques used were observation, interviews, and questionnaires. Data analysis techniques used were qualitative and quantitative data analysis. The results of this study are as follows: (1) The development of the KOJUMCAH media, which presents a storyline-based learning of mathematics for second-grade elementary students. (2) The feasibility of the product based on validation results shows a score percentage of 80.83% from the material expert, 98.61% from the media expert, and 98.61% from the second-grade teacher, indicating that the product falls under the